HUBUNGAN PENGETAHUAN, SIKAP, DAN MASA KERJA PADA PERAWAT TERHADAP PERILAKU MENCUCI TANGAN DI RUANG RAWAT INAP RSUD TUAN RONDAHAIM KABUPATEN SIMALUNGUN TAHUN 2020 - Ginting, Helpina Br (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Health workers who interact with the most and longest contact with patients in providing care one of them is a nurse. Nurses can have risks when interacting with patients, one of which is contracting or transmitting an infection. Nosocomial infections caused by health workers, including nurses, one of which occurs because of non-compliance with the application of the principles of standard precautins. The study aims to determine the relationship of knowledge, attitudes, and length of service of nurses to hand washing behavior in Tuan Rondahaim Regional Hospital, Simalungun Regency in 2020. The study used an analytic survey with cross sectional design. The population is all nurses in the Inpatient Room of Tuan Rondahaim Hospital, Simalungun Regency. The sampling technique uses total sampling method. Data analysis was performed by univariate, bivariate with chi square and multivariate analyzes with logistic regression tests at Î± = 0.05. The results of the study that there is a relationship of knowledge (p = 0,000), attitudes (p = 0,000) and the nurse's service period (p = 0,000) with hand washing behavior in RSUD Tuan Rondahaim Simalungun Regency in 2020. From the three Independent variables that are dominantly affecting washing behavior the hand is the attitude of the nurse. The conclusion of this study is that there is a relationship of knowledge, attitudes, and length of service of nurses to hand washing behavior in the Inpatient Room at RSUD Tuan Rondahaim, Simalungun Regency. It is recommended for nurses to continue to improve their knowledge of hand washing and always familiarize themselves with applying hand washing in the prevention of nosocomial infections. Should be taken into consideration in improving the knowledge and behavior of health workers must re-evaluate the effectiveness of hospital nosocomial infection prevention programs, especially regarding the compliance of health workers doing hand washing.